Development and Validation of the Biomedical Research Trust Scale (BRTS) in English and Spanish. (October 2016) - Baik, Sharon H.; Arevalo, Mariana; Gwede, Clement; Meade, Cathy D.; Jacobsen, Paul B.; Quinn, Gwendolyn P.; Wells, Kristen J.
This study developed and validated the Biomedical Research Trust Scale (BRTS), a 10-item measure of global trust in biomedical research, in English and Spanish (BRTS-SP). In total, 85 English- and 85 Spanish-speaking participants completed the BRTS or BRTS-SP, as well as measures of biobanking attitudes, self-efficacy, receptivity, and intentions to donate blood or urine. Results indicated the BRTS and BRTS-SP showed adequate internal consistency in both English and Spanish. In addition, greater levels of trust in biomedical research were significantly associated with greater self-efficacy, receptivity, attitudes, and intentions to donate blood and urine in English-speaking participants, and self-efficacy and intention to donate urine in Spanish-speaking participants. These results support the use of the BRTS and BRTS-SP among English- and Spanish-speaking community members.